2000
DOI: 10.1029/1999wr900308
|View full text |Cite
|
Sign up to set email alerts
|

Local reaction and diffusion in porous media transport models

Abstract: Abstract. The problem of when advection-dispersion models apply for reactive transport in porous media is addressed. Assuming local mass balances, including arbitrary homogeneous and interfacial chemical reactions, are known, volume averaging is applied to obtain a set of equations for the average concentrations. It is shown that timescale constraints must be satisfied in addition to the well-known length-scale constraint needed for volume averaging. The timescale for simulation must be longer than a diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This implies that it is only in transport regimes where homogeneous concentration fields form that laboratory-measured reaction rates be used directly. This is consistent with findings from other studies at other spatial scales (Mo and Friedly, 2000;Meile and Tuncay, 2006;Mohamed et al, 2006) where it was demonstrated that relatively fast reaction kinetics combined with low advection and diffusion rates can generate a scaling effect, and thus a discrepancy between lab and field rates.…”
Section: Discussionsupporting
confidence: 93%
“…This implies that it is only in transport regimes where homogeneous concentration fields form that laboratory-measured reaction rates be used directly. This is consistent with findings from other studies at other spatial scales (Mo and Friedly, 2000;Meile and Tuncay, 2006;Mohamed et al, 2006) where it was demonstrated that relatively fast reaction kinetics combined with low advection and diffusion rates can generate a scaling effect, and thus a discrepancy between lab and field rates.…”
Section: Discussionsupporting
confidence: 93%
“…A distinct impact of reactant segregation, with roughly 20-50% difference between measured rates and those calculated based on average concentrations was observed [21,45]. In diffusion dominated settings, a theoretical analysis suggested only minor effect for reactions taking place in the pore fluid [39]. However, sub-millimeter scale heterogeneity has been observed for O 2 and trace metals in sediments and microbial mats (e.g., [20,16]; see also [12]).…”
Section: Introductionmentioning
confidence: 95%
“…For Pe approximately equal to 1, the steady state was typically reached in 750,000 time steps. For Pe greater than 40, the error terms in the LB solute transport model become significant and the method is unstable [Noble, 1997].…”
Section: Lattice Boltzmann For Solute Transportmentioning
confidence: 99%